Thermodynamic Properties and Reversible Hydrogenation of LiBH4–Mg2FeH6 Composite Materials - Guanqiao Li; Motoaki Matsuo; Shigeyuki Takagi; Anna-Lisa Chaudhary; Toyoto Sato; Martin Dornheim; Shin-ichi Orimo (Inorganics, 2017)
In previous studies, complex hydrides LiBH4 and Mg2FeH6 have been reported to undergo simultaneous dehydrogenation when ball-milled as composite materials (1 − x)LiBH4 + xMg2FeH6. The simultaneous hydrogen release led to a decrease of the dehydrogenation temperature by as much as 150 K when compared to that of LiBH4. It also led to the modified dehydrogenation properties of Mg2FeH6. The simultaneous dehydrogenation behavior between stoichiometric ratios of LiBH4 and Mg2FeH6 is not yet understood. Therefore, in the present work, we used the molar ratio x = 0.25, 0.5, and 0.75, and studied the isothermal dehydrogenation processes via pressure–composition–isothermal (PCT) measurements. The results indicated that the same stoichiometric reaction occurred in all of these composite materials, and x = 0.5 was the molar ratio between LiBH4 and Mg2FeH6 in the reaction. Due to the optimal composition ratio, the composite material exhibited enhanced rehydrogenation and reversibility properties: the temperature and pressure of 673 K and 20 MPa of H2, respectively, for the full rehydrogenation of x = 0.5 composite, were much lower than those required for the partial rehydrogenation of LiBH4. Moreover, the x = 0.5 composite could be reversibly hydrogenated for more than four cycles without degradation of its H2 capacity.